Back Cover: In Situ Tetraethoxysilane‐Templated Porous Ba0.5Sr0.5Co0.8Fe0.2O3−δ Perovskite for the Oxygen Evolution Reaction (ChemElectroChem 2/2015). Issue 2 (1st July 2014) - Yang, Yisu; Zhou, Wei; Liu, Ruochen; Li, Mengran; Rufford, Thomas E.; Zhu, Zhonghua
<x xml:space="preserve">Abstract</x> A high‐surface‐area, porous Ba0.5Sr0.5Co0.8Fe0.2O3−δ perovskite was prepared by using an in situ template procedure, which exhibits activity for the oxygen evolution reaction that is 5.3 times the activity of conventional non‐porous one, as demonstrated by Z. Zhu et al. on p. 200.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>